Dinamika Intervensi Orang Tua dan Pengaruhnya terhadap Perceraian di Pengadilan Agama Purworejo - Anis Fuadah; Muhammad Mustahal; Septian Fiktor Riyantoro (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study discusses how parental intervention affects children's household conditions and contributes to the occurrence of divorce in the Purworejo Religious Court. The main question in this study is the forms of intervention that emerge and their impact on marital stability. This research was conducted in the study of the sociology of law and family dynamics, emphasizing the role of intergenerational relationships. The method used is qualitatively descriptive, through interviews with judges and analysis of case documents. This study identified the patterns of intervention that occurred. The results show that parental intervention can be divided into two types: constructive, which helps to defuse conflict, and destructive, which exacerbates the problem. Destructive forms of intervention, such as bias, pressure, or excessive control, have been shown to be more dominant in having a direct impact on the collapse of the marital relationship. These findings provide an explanation of the limitations of the role of parents in the child's household as well as the importance of family education and mediation strategies to reduce intergenerational conflicts.